DETERMINAN RETURN ON ASSET PADA PT. BANK MUAMALAT INDONESIA Tbk - Candra, Revi; Shabri, Husni; Azizah, Aprilia Nur; Fahlefi, Rizal (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to analyze the effect of Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), and Cash Turn-over on Return On Asset (ROA) at PT Bank Muamalat Indonesia (2012-2021). This research method uses a quantitative approach. The data source used is secondary data sources in the form of financial statements of PT Bank Muamalat Indonesia. The data analysis technique uses multiple linear regression analysis processed with the SPSS 26 program. The results showed that partially NPF and Cash Turnover had an effect on ROA with a significant value of 0.000 and 0.0009 respectively smaller than 0.05. CAR partially has no effect on ROA with a significant value of 0.151 greater than 0.05. Simultaneously NPF, CAR, and Cash Turn-over affect ROA at PT Bank Muamalat Indonesia with a significant value of 0.000 smaller than 0.05. Determinant of the influence of NPF, CAR and Cash Turn-over on Return On Asset is 55.1%.